Update on endoscopic endonasal resection of skull base meningiomas. Issue 4 (22nd December 2014) - Brunworth, Joseph; Padhye, Vikram; Bassiouni, Ahmed; Psaltis, Alkis; Floreani, Stephen; Robinson, Simon; Santoreneos, Stephen; Vrodos, Nick; Parker, Andrew; Wickremesekera, Agadha; Wormald, Peter‐John
<x xml:space="preserve">Abstract</x> Background The objective of this work was to report success rates as well as potential obstacles in transnasal endoscopic resection of anterior skull base meningiomas. Methods The study design was a case series with chart review at tertiary referral centers in South Australia and New Zealand. The patients were 37 consecutive patients who underwent endoscopic resection of skull‐base meningiomas between 2004 and 2013. Review of patient charts and operative details were performed. Outcomes including complications are reported. Results Eighty‐four percent of patients were women. There were 28 primary and 9 revision cases. Tumor locations were as follows: 14 olfactory groove/subfrontal; 12 planum/jugum sphenoidale; 7 tuberculum sellae; 3 clinoidal; and 1 clival. Vision change was the most common presenting symptom. Mean tumor volume was 33.68 cm3, mean diameter was 2.78 cm. Average operating times decreased with an initial learning curve and then plateaued. Primary tumors larger than 60 cm3 took an average of 10 hours to resect. Gross total removal was achieved in 29 patients. There were no perioperative deaths. Two deaths occurred within 1 year of surgery. Postoperative cerebrospinal fluid (CSF) leaks occurred in 13 patients. Seventy‐five percent of patients presenting with visual loss reported visual improvement. Of the 29 patients considered to have had complete resection at surgery, one was found to have residual disease on a postoperative magnetic resonance imaging (MRI) and another one later developed radiological evidence of recurrence. Conclusion Using a 2‐team approach, meningiomas of the skull base were successfully removed via an intranasal endoscopic technique. Although complete resection is typically possible even with large tumors, the lengthy resection required time for tumors larger than 60 cm3 (diameter ≥4 cm) may obviate some of the advantages of this approach. The rate of postoperative CSF leak decreases when a synthetic dural substitute is added but does not approach zero.